Discovery of previously unidentified genomic disorders from the duplication architecture of the human genome. - Sharp, A; Hansen, S; Selzer, R; Cheng, Z; Regan, R; Hurst, J; Stewart, H; Price, S; Blair, E; Hennekam, R; Fitzpatrick, C; Segraves, R; et al. (2006)
Genomic disorders are characterized by the presence of flanking segmental duplications that predispose these regions to recurrent rearrangement. Based on the duplication architecture of the genome, we investigated 130 regions that we hypothesized as candidates for previously undescribed genomic disorders. We tested 290 individuals with mental retardation by BAC array comparative genomic hybridization and identified 16 pathogenic rearrangements, including de novo microdeletions of 17q21.31 found in four individuals. Using oligonucleotide arrays, we refined the breakpoints of this microdeletion, defining a 478-kb critical region containing six genes that were deleted in all four individuals. We mapped the breakpoints of this deletion and of four other pathogenic rearrangements in 1q21.1, 15q13, 15q24 and 17q12 to flanking segmental duplications, suggesting that these are also sites of recurrent rearrangement. In common with the 17q21.31 deletion, these breakpoint regions are sites of copy number polymorphism in controls, indicating that these may be inherently unstable genomic regions.